Responsive website for self-assessment and career planning - Liu, Huijing (2018)
Career planning is a sophisticated procedure. With the development of psychology, behaviour test and personality test have been used to evaluate people’s career preference and provide career guidance. An effective and user friendly platform for career planning is required. This project aims to improve existing personality test websites and proposes a new career planning website which including personality test, career suggestion and skill development. To increase the accessibility and user friendliness of this website, Responsive Web Design (RWD) is used in this project. Users can access the website on smartphone, tablet and computer freely which page layout and content structure are remain constant in different resolution devices. In this report, the existing personality test website will be assessed and new features and technology details of the new career planning website will be discussed.